Electrolytic Formation of Crystalline Silicon/Germanium Alloy Nanotubes and Hollow Particles with Enhanced Lithium‐Storage Properties. Issue 26 (9th May 2016) - Xiao, Wei; Zhou, Jing; Yu, Le; Wang, Dihua; Lou, Xiong Wen (David)
Abstract: Crystalline silicon(Si)/germanium(Ge) alloy nanotubes and hollow particles are synthesized for the first time through a one‐pot electrolytic process. The morphology of these alloy structures can be easily tailored from nanotubes to hollow particles by varying the overpotential during the electro‐reduction reaction. The continuous solid diffusion governed by the nanoscale Kirkendall effect results in the formation of inner void in the alloy particles. Benefitting from the compositional and structural advantages, these SiGe alloy nanotubes exhibit much enhanced lithium‐storage performance compared with the individual solid Si and Ge nanowires as the anode material for lithium‐ion batteries. Abstract : Li likes alloys : Crystalline SiGe alloy nanotubes and hollow particles are synthesized through a one‐pot electrolytic process in molten salts. The solid‐diffusion process, governed by the nanoscale Kirkendall effect, leads to the formation of internal voids in the SiGe alloy particles. Owing to the unique structural features and desirable composition, the SiGe alloy nanotubes exhibit enhanced lithium‐storage performance.